Strategic Political Communication of The Winning Candidate in Cirebon City’s Regional Election - Syahdani, Mochamad Adam; Rahmandika, Rizal; Khumayah, Siti; Hermawan, Abdul Jalil (Equivalent: Jurnal Ilmiah Sosial Teknik, 2025)
The election of the Cirebon Mayoral Candidate and the Cirebon Deputy Mayoral Candidate in 2024 provides an important picture of the implementation of political communication strategies in regional head election campaigns. Choosing the right communication strategy plays a vital role in attracting public sympathy and determining their political choices. This study aims to explore how Candidate Pair 03 Effendi Edo and Siti Farida Rosmawati design and implement communication strategies that can build emotional connections with voters and influence the political preferences of Cirebon residents. Political communication theory is used to analyze media selection, narratives, and the relevance of messages conveyed to the public. A qualitative research method with a case study approach was chosen to obtain data through interviews with the campaign team and analysis of social media content and campaign materials. The results of the study show that Candidate Pair 03 Effendi Edo and Siti Farida Rosmawati succeeded in establishing emotional closeness with the community through a local-based approach that focuses on community empowerment, thus impacting voters' political choices.